ANALISIS KUALITAS LAYANAN, KUALITAS HUBUNGAN DAN KEPUASAN NASABAH TERHADAP NILAI NASABAH (STUDI KASUS PADA DEBITUR KREDIT USAHA MIKRO PT BANK MANDIRI UNIT JAKARTA PETUKANGAN) - Latif, Adi Sofyana (Aksara Public, 2019)
This study is a regression analysis with the results Quality of Service, Quality and Value Customer Relationship positive effect on satisfaction and significant (quality of service, quality of relationships) and to the value of customers (not significant). The goal is to analyze the influence of service quality, relationship quality and customer value on customer satisfaction, both directly and indirectly. The unit of analysis of this study is the borrowers who apply for micro, analytical method with quantitative analysis. Techniques of analysis using multiple linear regression analysis, followed by analysis of determination (R Square), hypothesis testing either partially (t test) and simultaneous (F test). Prior to analysis by multiple linear regression test beforehand in the research instrument (questionnaire) with validity and reliability as well as classical assumptions. After all the results of the analysis meet the new criteria forwarded at this stage of regression. Analysis tool application program SPSS version 22.0.